THE EFFECT OF GIVING FERMENTATION FLOWS OF PINANG LEAF (Areca cathecu L.) AND SURIAN LEAVES (Toona sinensis ROXB.) TO LELE FISH PAINT (Clarias gariepinus Var.) - Widia Saputri (Serambi Biologi, 2018)
Catfish (Clarias gariepinus L.) is a type of consumption fish from fresh water with elongated body and slippery skin. Efforts to increase catfish cultivation are characterized by high stocking density followed by increased use of artificial feed that is rich in protein. Catfish disease is one of the problems that are often encountered in the effort to enlarge catfish. Therefore, an alternative cure is used with areca leaf liquid fermentation (Areca cathecu L.) and surian leaves (Toona sinensis ROXB.). This study was an experimental study, using a factorial complete randomized design consisting of two factors, namely the dosing factor (A) and the length of the observation day (B). Each treatment was repeated 6 times. The data of this study were analyzed using Analysis Of Variants (ANOVA), the results were significantly different continued using the DNMRT advanced test with a level of 5%. Based on the research conducted, it can be concluded that the use of areca leaf (Areca cathecu L.) and surian leaf (Toona sinensis ROXB.) liquid fermentation influences the wound healing in catfish (Clarias gariepinus Var.) and the most optimal dose to assist the healing process is at a dose of 15 ml.